Biomarkers of Oxidative Stress as Indicators of Fungi Environmental Pollution in Balb/c Albino Mice Monitored from South West, Nigeria. (7th April 2019) - Odebode, Adeyinka; Adekunle, Adedotun
Abstract : The presence and detection of common airborne fungi in an area are important for the prevention and treatment of allergic fungal diseases. Because of the ubiquitous nature of fungi, the effect of four different fungal species in production of antioxidant and reactive oxygen species production in balb/c albino mice was investigated. Fifty-four balb/c mice were randomly divided into eight groups (n = 6) and a normal control group. Four different fungal plates, comprising Aspergillus flavus, Aspergillus penicillioides, Penicillium citrinum, and Penicillium chrysogenum, which were the most abundant fungi species sampled in the environment were cultured for one week to make 2.3 x 10 7 and 3.2 x 10 5 spores and injected intranasally in sterile saline into the nostrils of each of the mice. Results showed that all fungal inoculated organism produced statistically (P<0.05) significant reactive oxygen species while antioxidant parameters were significantly decreased in a dose dependent manner compared with normal control mice. It is therefore concluded that Aspergillus flavus, Aspergillus penicillioides, Penicillium citrinum, and Penicillium chrysogenum can alter and decrease immune function in balb/c mice. Therefore, this study was conducted to identify the most common airborne fungal species present in Southwest Nigeria and to study their allergic reactions.